KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS SANGURARA KECAMATAN TATANGA KOTA PALU - Irmawati, Sri (Katalogis, 2017)
The purpose of this study was to determine the quality of health services at Sangurara Public Health Center of Tatanga District Palu City referring to the theory of Zeithaml in Ratminto and Winarsih (2005:175-176), stating that to evaluate the quality of public services, the public generally uses five (5) dimensions, namely reliability, responsiveness, assurance, emphaty, and tangibles (physical evidence). This study used qualitative descriptive type of research with inductive data analysis and used informants of research consisting of the functional officers assigned to provide services at Sangurara Public Health Center of Tatanga District; the administrative staff at Sangurara Public Health Center of Tatanga District; and the user community of health services at Sangurara Public Health Center of Tatanga District as the sources of primary data. Data analysis technique used by the researcher was descriptive data analysis, with the results showed that: (1) The quality of health services at Sangurara Public Health Center of Tatanga District seen from the dimensions of reliability, responsiveness, and emphaty had been in line with public expectations, while from the dimensions of assurance and tangibles (physical evidence) had not yet met public expectations so it still needed to be addressed.